2019
DOI: 10.3390/jfmk4020039
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cardiometabolic Responses to Multi-Modal Integrative Neuromuscular Training in Children

Abstract: Integrative neuromuscular training (INT) has emerged as an effective strategy for improving health- and skill-related components of physical fitness, yet few studies have explored the cardiometabolic demands of this type of training in children. The aim of this study was to examine the acute cardiometabolic responses to a multi-modal INT protocol and to compare these responses to a bout of moderate-intensity treadmill (TM) walking in children. Participants (n = 14, age 10.7 ± 1.1 years) were tested for peak ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…Thus, these findings provide evidence that cardiorespiratory stress is high during this type of high-intensity, sport-specific circuit training. Interestingly, a very recent study compared the acute effects of an integrative neuromuscular training program for 12 min (2 sets × 6 exercises × 30 s each with equal rest) on cardiometabolic responses of 10-11 year old children [15]. In that study, the increase of HR was lower than in the present study and HR ranged between 61% and 92% of HR max [15].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Thus, these findings provide evidence that cardiorespiratory stress is high during this type of high-intensity, sport-specific circuit training. Interestingly, a very recent study compared the acute effects of an integrative neuromuscular training program for 12 min (2 sets × 6 exercises × 30 s each with equal rest) on cardiometabolic responses of 10-11 year old children [15]. In that study, the increase of HR was lower than in the present study and HR ranged between 61% and 92% of HR max [15].…”
Section: Discussioncontrasting
confidence: 55%
“…Interestingly, a very recent study compared the acute effects of an integrative neuromuscular training program for 12 min (2 sets × 6 exercises × 30 s each with equal rest) on cardiometabolic responses of 10-11 year old children [15]. In that study, the increase of HR was lower than in the present study and HR ranged between 61% and 92% of HR max [15]. Importantly, in that study, VO 2 during the 12 min exercise was increased from 28% to 64% VO 2max , suggesting that HR is indicative of oxygen uptake in this type of protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternating training methods may help alleviate the overtraining effect caused by repeated high-load activities. Previous studies have shown that integrative neuromuscular training has a positive effect on balance ability [ 58 – 60 ], speed capability [ 10 , 61 , 62 ], muscle strength, muscle endurance, and flexibility [ 63 ] of the practitioner. Strength, balance, and body coordination contribute to the development of participant's motor skills and physical fitness, which is essential for building a healthier life.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, physical activity promotion efforts should include strength-building activities owing to its potent skill-building, performance-enhancing, and injury-reducing effects (3,57,74). An acute bout of resistance training that included body weight, medicine ball, and battling rope exercises resulted in an exercise intensity of 61% to 92% of maximum heart rate in healthy children (81). These findings suggest that well-designed resistance training programs can enhance neuromuscular fitness and contribute to the recommended 60 min or more of MVPA daily.…”
Section: Underrated Benefits Of Youth Resistance Exercisementioning
confidence: 99%